The Influence of Leadership Style in Increasing Work Motivation on Employee Performance at The Office of The Regional Revenue and Financial Management Agency of The Northern Luwu District - Eka Saputri; Suparni sampetan; Sukri Sukri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
The purpose of this study was to determine how much leadership style and work motivation affect employee performance at the office of the regional financial and revenue management agency of North Luwu Regency. The type of research used in this research is quantitative. The population of this study were employees at the office of the regional financial and revenue management agency of North Luwu Regency. Where the sample was collected by sampling technique. The total sample was calculated using the Slovin formula resulting in a sample of 55 respondents. The data analysis techniques used are instrument tests, multiple linear regression analyses, and coefficient of determination analysis. The results showed that the leadership style variable (X1) partially had a significant effect on employee performance (Y) while the work motivation variable (X2) partially had a significant effect on employee performance (Y).